Psychiatric Advance Directives, a Possible Way to Overcome Coercion and Promote Empowerment - Khazaal, Yasser; Manghi, Rita; Delahaye, Marie; Machado, Ariella; Penzenstadler, Louise; Molodynski, Andrew (Frontiers in Public Health, 2014)
Psychiatric advance directives (ADs) allow an individual to state their preferences for future treatment at times when they may be unable to make considered decisions. There are differences in their form and legal value and the process associated with their use and completion. Several studies have now been completed to assess the impact of advance directives on service use and coercion. Their results give a mixed picture but directives nevertheless have the potential to support the empowerment process, minimize experienced coercion, and improve coping strategies. These may in turn reduce the frequency of in-patient service use. Further studies on the different processes of facilitation involved and on different populations are necessary to improve our knowledge and use of these potentially powerful interventions.